Peran Pemerintah Desa dalam Pemberdayaan Masyarakat Melalui Program Badan Usaha Milik Desa (BUMDes) Desa Semaran Kecamatan Pauh Kabupaten Sarolangun - Astrid Kinanti Putri; Hendriyaldi Hendriyaldi; Ovie Yanti (PPIMAN Pusat Publikasi Ilmu Manajemen, 2026)
The empowerment of rural communities is a strategic effort to improve the well-being and economic self-reliance of communities in rural areas. One of the instruments developed by the government to support this objective is the establishment of Village-Owned Enterprises (BUMDes) as economic institutions managed by the village and the community in a participatory manner. This study aims to analyze the role of BUMDes in Semaran Village, Pauh Subdistrict, Sarolangun Regency, in empowering the rural community through the management of local potential, the development of productive business units, and the increase in community income. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and analysis of various business programs run by BUMDes. The results indicate that the Semaran Village Government plays a crucial role as a facilitator, initiator, mentor, and supervisor in the management of BUMDes Maju Bersama. The village government is involved in providing initial capital, institutional development, and training to enhance community capacity. Supporting factors for success include Village Fund support, visionary leadership from the Village Head, and active community participation. The main challenges faced include limited capital, a lack of business innovation, low human resource capacity, and limited market access. However, with effective and sustainable management, BUMDes have the potential to serve as a driving force for rural economic development as well as a means of inclusive and sustainable community empowerment.